Language and Power Relations in Selected Marriage Ceremonies’ Songs among the Agĩkũyũ and Akamba Communities of Kenya - Kinuthia, J. W.; Gachari, R.; Wambua, B. (International Journal of Culture and History, 2024)
The genre of songs is a critical component of marriage discourse among many African communities. Language use in the songs within this premise is a means of conveying messages that enable the participants to express some commonsense assumptions that are implicit in the conventions according to which people interact linguistically. The focus of this paper is to illuminate the connections between language and elements of social life such as gender and power within this social practice and how these may define a society’s worldview, articulate societal consciousness, social emancipation and enhancement of social justice. A random sample of marriage ceremony songs from the two communities have been analyzed with a view of discussing how language within this discourse context has been used to give shape and meaning to the world, how language constructions are central in drawing the relationships between language and thought, how we understand abstract meanings and how context influences meaning. The study is grounded on the principles of Wodak and Meyer’s (2004) Discourse Historical Approach where expressions in the songs have been qualitatively examined leading to the argument that language is significant in the production and maintenance of social relations of power and this contributes to the shaping of societal understanding, thoughts and feelings, defining people’s relationships with each other, establishing the kind of speech that one is involved in as well as describing societal ideologies. The findings of this paper are of benefit to leaders and policy makers in our society who are charged with the responsibility of guiding the development of indigenous knowledge systems for posterity. The general public too as consumers of cultural knowledge would benefit from these insights since they contribute to their understanding of the perceptions and meanings embedded in the songs that they so love to participate in.